Realita Kesadaran dan Tantangan Pajak Dikalangan Generasi Z Sidoarjo dan Surabaya - Achmad Wicaksono; Anindita Putri Novinda; Rif’atul Choiriyyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Tax awareness has become an important aspect in the modern era, especially in the context of generation Z who increasingly understand the urgency of their contribution to the tax system. This article explores generation Z's tax awareness, focusing on their understanding of tax obligations and the challenges they face in the modern era. Generation Z, with easy access to information, has great potential to shape taxpayer compliance, but various challenges such as lifestyle changes, global economic transformation, and the complexity of tax regulations are factors that influence their compliance. By understanding these dynamics, it is hoped that a more comprehensive view can be produced regarding the role of Generation Z in creating taxpayer compliance and supporting future economic development. The research method used by researchers is descriptive quantitative method. Data collection used by researchers was carried out using a questionnaire-based survey method. The research results obtained are the factors that influence compliance in paying taxes in this generation Z era, namely because they realize that taxes are one of the government's supports in carrying out regional development, so that everyone needs to pay taxes. This shows that the level of tax knowledge is an important factor in increasing taxpayer compliance to fulfill their tax obligations. Their challenge in paying taxes is that they find it difficult to set aside special funds to pay taxes. This is because generation Z may not have sufficient financial knowledge or literacy to plan and manage their funds wisely and live a high lifestyle.